Análise de redes de abastecimento de biomassa com resíduos densificados - Possidônio, Elisangela Fernandes da Silva Campana (Universidade Federal de São Carlos, 2015)
Biomass has acquired increasing importance as an alternative energy source. The fact of it being considered one of the main alternatives for diversification of energy sources and reducing dependence on fossil fuels, has increased its market acceptance. Despite of being a cheap and renewable source and Brazil being a large production of agricultural and forestry biomass, the use of such waste find some barriers; because of low density and low energy efficiency, which can increase the cost to use. The densification of biomass has drawn attention due to the superiority of the biomass in nature, in relation to the physical characteristics and the characteristic combustion. This work aims in a general way, studies how occurs the distribution of biomass from the product available local to the points of consumption, more specifically to assess the impact of biomass densification in the distribution operations and on transport costs. As a complement, a goal is to make a comparative study of supply with renewable fuel and non-renewable, more specifically with natural gas. For the characterization of supply networks and data collection were carried out visits to companies in this kind of industry, and to compare the costs in distribution operations, it was used a transport model. The results of the comparative study of the scenarios presented the possibility of reduction of 51-60% in transport costs and a 63% reduction in the number of vehicles used for the supply network. However, the cost of densified materials increased total cost in 41.6% in relation to waste in nature. In the comparative study of supply with renewable and nonrenewable fuel materials considered in the study showed economic advantages over natural gas.
Biomass supply network analysis with densified waste
Keywords: rede de abastecimento; modelagem matemática; transporte; densificação; logística empresarial; biomassa - energia; modelos matemáticos; supply network; mathematical modeling; transpotation; densification; ENGENHARIAS::ENGENHARIA DE PRODUCAO